2000
DOI: 10.1177/01461672002612012
|View full text |Cite
|
Sign up to set email alerts
|

Affect and Stereotypic Thinking: A Test of the Mood-and-General-Knowledge Model

Abstract: Happy, sad, or neutral participants evaluated the likelihood of a suspect’s guilt. The suspect’s membership was or was not stereotypically associated with the misconduct of which he was accused. Participants also were provided with specific case information that varied in its implications (ambiguous implying either the suspect’s guilt or innocence). The results show that when stereotypes clearly contradict specific information, happy people rely on the latter and no longer use stereotypes. The general assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 41 publications
2
54
1
Order By: Relevance
“…Rather, they are likely the result of positive affect signaling that it is appropriate to rely on general trait information as a basis for forming an impression. Thus, individuals in happy moods may integrate trait and behavioral information (e.g., Bless, Schwarz, & Wieland, 1996;Krauth-Gruber & Ric, 2000), an idea that is consistent with participantsÕ reports about the type of information that they relied upon. It is not clear, however, if these reports reflect ''real'' differences in reliance on trait and behavioral information, or whether they are retrospective evaluations of the extent to which different types of information influenced their judgments.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Rather, they are likely the result of positive affect signaling that it is appropriate to rely on general trait information as a basis for forming an impression. Thus, individuals in happy moods may integrate trait and behavioral information (e.g., Bless, Schwarz, & Wieland, 1996;Krauth-Gruber & Ric, 2000), an idea that is consistent with participantsÕ reports about the type of information that they relied upon. It is not clear, however, if these reports reflect ''real'' differences in reliance on trait and behavioral information, or whether they are retrospective evaluations of the extent to which different types of information influenced their judgments.…”
Section: Discussionsupporting
confidence: 55%
“…These results suggest that happy individuals did not ignore the individuating information, but rather attempted to relate it to the targetÕs category membership. Thus, happy participantsÕ processing appeared to be no less ''systematic'' than sad participantsÕ (see Bless, Schwarz, & Wieland, 1996;Krauth-Gruber & Ric, 2000).…”
Section: The Affect-as-information Modelmentioning
confidence: 99%
“…In similar mock-juror social-judgment tasks happiness increased stereotyping of Hispanics, student-athletes , priests, and skinheads (Krauth-Gruber & Ric, 2000). 2 Study 3 found that increased stereotyping related to happy mood extends to gender stereotypes and adds to the already-substantial body of evidence demonstrating that happiness often increases stereotyping (e.g., Park & Banaji, 2000).…”
Section: Theoretical Implicationsmentioning
confidence: 92%
“…Specifically, when provided with both category and individuating information, judgments of happy individuals reflected the implications of the category information more than judgments of neutral or sad participants (Bodenhausen et al, 1994b). These and other related findings (e.g., Bless et al, 1996b;Krauth-Gruber and Ric, 2000;Park and Banaji, 2000;Ric, 2004) demonstrate an increased reliance on the category information under happy moods, unless the individuating information is extremely different from the category information (Krauth-Gruber and Ric, 2000). Various accounts have been proposed for these effects and other related evidence suggesting an increased use of heuristics under happy moods.…”
Section: Mood As a Moderator Of Brand Extension Evaluationsmentioning
confidence: 58%
“…However, based on the existing affect and cognition literature, it may be assumed that a stronger reliance on general knowledge structures for happy compared to neutral or sad mood states is at its roots (Bless et al, 1996a). Contrary to the assumptions of capacity or motivational deficits, the notion of increased reliance on general knowledge structures would imply that despite a positive mood state, no assimilation effects emerge for extreme deviations between category and exemplar information, as suggested upon different reasoning by Aaker and Keller (1990) (for parallel effects in the domain of stereotype research, see Krauth-Gruber and Ric, 2000).…”
Section: Discussionmentioning
confidence: 99%